Особливості формування обмежень на землях гірничо-видобувної промисловості - Чумаченко, Олександр Миколайович; Гурбанова, Анна Рустамівна (НУБІП України, 2024)
Abstract. Mining land plays a critical role in Ukraine’s economic development, especially amid armed conflict and post-war recovery. Effective management through usage restrictions is vital. This study explores the formation of these restrictions and their impact on territorial organization. Key objectives include analyzing legal frameworks, identifying specific constraints, and offering improvement recommendations. Findings emphasize the necessity for a systematic approach, modern technology integration, and stakeholder involvement. Future research should focus on enhancing environmental impact assessment methods and developing innovative land restoration solutions. This study uses the example of the Shmatkivske granite deposit to illustrate practical applications.
Keywords: економічний розвиток; нормативно-правова база; гірничо-видобувна промисловість; земельні ресурси; economic development; regulatory framework; mining industry; land resources